Activity of Thymus capitatus essential oil components against in vitro cultured Echinococcus multilocularis metacestodes and germinal layer cells. Issue 7 (12th April 2019) - Hizem, Amani; Lundström-Stadelmann, Britta; M'rad, Selim; Souiai, Sawssen; Ben Jannet, Hichem; Flamini, Guido; Ascrizzi, Roberta; Ghedira, Kamel; Babba, Hamouda; Hemphill, Andrew
Abstract: The essential oil (EO) of Thymus capitatus, seven fractions (F1–F7) obtained from silica gel chromatography, and several pure EO components were evaluated with respect to in vitro activities against Echinococcus multilocularis metacestodes and germinal layer (GL) cells. Attempts to evaluate physical damage in metacestodes by phosphoglucose isomerase (PGI) assay failed because EO and F1–F7 interfered with the PGI-activity measurements. A metacestode viability assay based on Alamar Blue, as well as transmission electron microscopy, demonstrated that exposure to EO, F2 and F4 impaired metacestode viability. F2 and F4 exhibited higher toxicity against metacestodes than against mammalian cells, whereas EO was as toxic to mammalian cells as to the parasite. However, none of these fractions exhibited notable activity against isolated E. multilocularis GL cells. Analysis by gas chromatography-mass spectrometry showed that carvacrol was the major component of the EO (82.4%), as well as of the fractions F3 (94.4%), F4 (98.1%) and F5 (90.7%). Other major components of EO were β -caryophyllene, limonene, thymol and eugenol. However, exposure of metacestodes to these components was ineffective. Thus, fractions F2 and F4 of T. capitatus EO contain potent anti-echinococcal compounds, but the activities of these two fractions are most likely based on synergistic effects between several major and minor constituents.